Joint electroreduction of lanthanum, gadolinium and boron in halide melts - Khushkhov KH.B.; Vindizheva M.K.; Uzdenova A.S.; Zhanikaeva Z.A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The joint electroreduction of La, Gd and B from chloride-fluoride melts has been studied by cyclic voltametry. Based on the analysis of voltamograms the possibility of electrosynthesis of lanthanum-gadolinium borides from chloride-fluoride melts has been shown.